Advancing EIA framework for deep-sea mining: a critical review of current regulations and proposals - Yu Ning; Yu Ning (Frontiers in Marine Science)
On June 25, 2021, Nauru informed the Council of International Seabed Authority that its sponsored entity Nauru Ocean Resources Inc. intended to apply for approval of a plan of work for exploitation in the international seabed area and requested the Council to complete the adoption of relevant regulations, triggering the “two-year rule”. This has intensified the urgency to finalize the Exploitation Regulations as the current draft regulations remain insufficient to address the environmental challenges posed by mining activities. Deep-see mining may have an irreversible impact on the marine environment, with disputes centred on how to effectively implement environmental impact assessment to improve environmental protection. The current regulatory texts, including the 2024 Revised Consolidated Text, exhibit significant limitations, particularly in the areas of environmental risk assessment, alternatives, cumulative impact assessment, and stakeholder participation within the environmental impact assessment framework. It highlights the need for clear review standards and quantitative models for environmental risk assessment, well-defined scopes and review mechanisms for alternatives, precise definitions and processes for cumulative impact assessment, and robust stakeholder engagement mechanisms. These recommendations are essential for developing a comprehensive legal mechanism that can effectively address the environmental challenges associated with deep-sea mining activities, thereby contributing to the sustainable management of the resources in “the Area”.